2014
DOI: 10.1016/j.rbo.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida após artroplastia total do joelho: revisão sistemática

Abstract: r e v b r a s o r t o p . 2 0 1 4;4 9(5):520-527 w w w . r b o . o r g . b r Artigo OriginalQualidade de vida após artroplastia total do joelho: revisão sistemática ଝ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 40 publications
0
9
0
5
Order By: Relevance
“…The trial population predominantly included patients with severe preoperative symptoms, as shown by low mean quality of life utility values at baseline 7. Many previously published uncontrolled before-after studies showed similarly large effects 89 In particular, the systematic review by Shan and colleagues described 19 studies that showed substantial improvements from baseline status, both in the intermediate and long term, for disease specific and generic health related quality of life across a broad range of domains 9.…”
Section: Introductionmentioning
confidence: 99%
“…The trial population predominantly included patients with severe preoperative symptoms, as shown by low mean quality of life utility values at baseline 7. Many previously published uncontrolled before-after studies showed similarly large effects 89 In particular, the systematic review by Shan and colleagues described 19 studies that showed substantial improvements from baseline status, both in the intermediate and long term, for disease specific and generic health related quality of life across a broad range of domains 9.…”
Section: Introductionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) provides a significant improvement in the quality of life for knee osteoarthritis patients [3,4,5]. As life expectancy and activity levels in the elderly increase in industrialised countries, TKA is becoming even more popular [6].…”
Section: Introductionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is a widely used surgical procedure [1, 2]. In 2014, Germany’s incidence of TKA was 197 per 100,000 inhabitants, which was the second highest rate in Europe [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although TKA is generally considered cost-effective [3, 4] and improved function, mobility and quality of life [1, 3, 5, 6], a subset of patients report prolonged pain, functional impairment [7] or remain dissatisfied with outcomes [8–12].…”
Section: Introductionmentioning
confidence: 99%